Tissue Specific Heterogeneity in Effector Immune Cell Response - Tufail, Saba; Khan, Farheen B.; Sherwani, Asif; Gupta, Umesh D.; Owais, Mohammad (Frontiers in Immunology, 2013)
Post pathogen invasion, migration of effector T-cell subsets to specific tissue locations is of prime importance for generation of robust immune response. Effector T cells are imprinted with distinct ‘homing codes’ (adhesion molecules and chemokine receptors) during activation which regulate their targeted trafficking to specific tissues. Internal cues in the lymph node microenvironment along with external stimuli from food (vitamin A) and sunlight (vitamin D3) prime dendritic cells, imprinting them to play centrestage in the induction of tissue tropism in effector T cells. B cells as well, in a manner similar to effector T cells, exhibit tissue tropic migration. In this review, we have focused on the factors regulating the generation and migration of effector T cells to various tissues alongwith giving an overview of tissue tropism in B cells.